Simulation Study of Gallium Nitride (GaN) Based Inverter for Electric Vehicle Application Using MATLAB - Ching, Wei Lun; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2022)
Eco-friendly has become the first consideration in developing new innovative technology in the automotive field. The fundamental change to archive the aim of eco-friendly is replacing non-renewable energy. However, when dealing with the conversion of power, the energy loss in the process is not ignorable. This paper presented a test to prove advanced semiconductors’ performance in building a power device. This study aims to analyze and compare the performances of exiting advanced semiconductors like Gallium Nitride and Silicon Carbide, those semiconductors have a similarity which is wide band gap semiconductors. The experimental method to investigate the performance of those semiconductor-based inverters will be entirely based on MATLAB simulation software. The comparison aspect is based on each semiconductor-based inverter’s switching and conduction loss. As a result of this thesis, the performance of Gallium Nitride dominates in lowering each loss, and by using GaN MOSFET as the material to build the inverter, the total inverter loss able reduced the loss by 22.73% compared to the inverter built by using SiC MOSFET. The study increases its accuracy by introducing different tests under various temperatures and replacing the load of the inverter with a motor model to obtain even more performance analysis information.